2021
DOI: 10.1111/jfbc.13850
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ophiopogonis Radix from different producing areas by headspace‐gas chromatography‐ion mobility spectrometry analysis

Abstract: Ophiopogonis Radix can be divided into Zhemaidong (ZMD) and Chuanmaidong (CMD). The main planting areas of ZMD are Cixi City and Sanmen county. The quality and price of Ophiopogonis Radix from different producing areas are different. In this study, the headspace‐gas chromatography‐ion mobility spectrometry (HS‐GC‐IMS) method is used to rapidly identify ZMD and CMD. The method is also used to identify ZMD from Cixi and Sanmen by analyzing volatile organic compounds (VOCs). A total of 58 VOCs was obtained from Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…For example, HS-GC-IMS was successfully used for reliable classification of geographical origins for both olive oil (EVOO) [ 38 ] and wine [ 39 ]. Furthermore, the HS-GC-IMS method was applied to quickly identify Ophiopogonis Radix from different regions [ 40 ]. Moreover, HS-GC-IMS has also been used to determine the geographical origins of “Chenpi” [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, HS-GC-IMS was successfully used for reliable classification of geographical origins for both olive oil (EVOO) [ 38 ] and wine [ 39 ]. Furthermore, the HS-GC-IMS method was applied to quickly identify Ophiopogonis Radix from different regions [ 40 ]. Moreover, HS-GC-IMS has also been used to determine the geographical origins of “Chenpi” [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ker-Gawl, belongs to the Liliaceae family and is commonly applied as traditional Chinese medicine (TCM) documented in the clinical. Maidong (MD) was first mentioned in Variorum of Shennong’s Classic of Materia Medica (Shennong Bencao Jing) with the effect of nourishing yin and generating body fluid, moistening the lung and clearing the heart [ 7 , 8 ]. Additionally, modern phytochemical studies have suggested that MD is rich in various compounds, including steroidal saponins, homoisoflavonoids, and polysaccharides, which exhibit cardiovascular protection, anti-cancer, immunomodulatory, anti-inflammatory, central nervous system protective, antioxidative, and anti-diabetes effects [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…HS-GC-IMS has a good application in the detection of flavor components in the food field, and has been increasingly widely used in the field of pharmaceutical research in recent years. Jia He used HS-GC-IMS method for the identification of adulterated inferior products in Ophiopogon, and this method showed a higher degree of identification [ 36 ].…”
Section: Introductionmentioning
confidence: 99%